Web-based Application for Doctor-Patient Appointment Management System - S., Raj Kumar; S., Shadheem; S., Surya (Journal of ISMAC, 2024)
The proposed Doctor Appointment System (DAS) aims to significantly improve the administration process and patient access to healthcare with a user-friendly interface. DAS utilizes advanced technologies to develop a web interface that makes it simple for patients to make appointments with medical professionals in real time. Patients can search for the doctor availability, specialized doctors, and available appointment slots using the portal, and book appointments directly through the portal. Additionally, the DAS forwards automated reminders to patients and physician about their appointments, enabling them to save their scheduled appointments in a customizable profile. Furthermore, the medical data in DAS are protected with strong data security procedures to ensure that the patients’ private information is safe. The proposed DAS is integrated with the Electronic Health Record (EHR) systems to provide real-time updates on the available doctors and slots. The user interface developed helps patients and the doctors to easily manage their appointments in an efficient and secure way.
Keywords: Web Interface; Doctor Appointment; EHR; Priority Scheduling; Authentication; Inbuilt Security